Ernährungsverhalten von weiblichen und männlichen Hochleistungsturnern - Schwidergall, S.; Weimann, E.; Witzel, C.; Molenkamp, G.; Brehl, S.; Bohles, H. (Wiener Medizinische Wochenschrift, 1998)
Elite gymnasts pass through their whole physical and intellectual development with intensive physical training. In this period malnutrition can lead to delayed pubertal development with insufficient growth spurt and an increased incidence of stress fractures or osteoporoses. Different aspects about nutrition like body composition, objective and subjective eating-behaviour and sex-specific differences will be evaluated in our study. We examined 22 elite female gymnasts (age: median = 13.5 [12.0-16.1] years) und 19 elite male gymnasts (age: median = 12.3 [10.1-14.8] years). The following anthropometric measurements were carried out: weight, length, body mass index, upper arm circumference, arm muscle area, triceps skinfold, arm fat area. Eating diaries were compared with the recommendations of the German Federation of Nutrition and subjective eating behaviour was evaluated by questionnaires. Measurement of body composition showed an increase of musclemass at the cost of fatmass. The girls were smaller and leaner than the boys. Caloric intake in both groups was insufficient. Moreover the girls showed a tendency towards pathologic eating behaviour.